Does managerial discretion affect debt maturity in Chilean firms? An agency cost and asymmetric information approach (2016)
We address debt maturity determinants for Chilean firms using data whose information was drawn from the Longitudinal Survey of Companies (ELE). Results from pooled Tobit regressions indicate that for firms with high growth opportunities, managerial discretion will encourage longer debt terms, a decision that contributes to reducing liquidity risk. For firms with low growth opportunities, managerial discretion does not affect debt maturity, while external monitoring reduces it. These results provide new evidence for international literature. Other conclusions suggest that debt maturity is positively related to firm size, capital structure, and asset tangibility and negatively related to agency costs and membership in a holding company. These findings are consistent with international studies.